EDUCATION FOR ALL: TRANSFORMING EDUCATION FOR A BETTER FUTURE - Kindy, Aulia; Zamroni, Zamroni; Tamam, Badrut; Solekhin, Muhammad (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study explores the implementation of Internal Quality Assurance (IQA) systems in Islamic boarding schools (pesantren) in Indonesia, focusing on the challenges and opportunities of integrating these systems within the unique cultural and religious context of pesantren. Given the dynamic educational landscape and the evolving demands of quality education, this research seeks to understand how IQA can be effectively adapted to fit the specific needs of pesantren while ensuring that their traditional pedagogical values are preserved. The study employs a qualitative research approach, including an analysis of relevant literature and in-depth interviews with key stakeholders involved in the development and implementation of IQA systems within pesantren. The findings reveal that successful IQA implementation requires a careful balance between modern educational standards and the intrinsic values of pesantren, such as religious education, spiritual development, and character formation. Moreover, the study identifies several critical factors for effective IQA implementation, including strong leadership, stakeholder engagement, capacity building for educators and administrators, and the strategic use of technology to enhance efficiency and data management. Furthermore, the research emphasizes the importance of fostering a culture of continuous improvement and community involvement, which includes engaging parents, alumni, and local community members in the IQA process. By addressing these key factors, pesantren can not only enhance the quality of their educational programs but also contribute to the broader goal of developing a knowledgeable and skilled workforce that aligns with the needs of a rapidly changing global landscape. Ultimately, this study advocates for a holistic approach to IQA in pesantren that preserves their cultural heritage while embracing innovation to meet the demands of the 21st century.